2012
DOI: 10.4103/0970-0358.101309
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric oxygen and wound healing

Abstract: Hyperbaric oxygen therapy (HBOT) is the use of 100% oxygen at pressures greater than atmospheric pressure. Today several approved applications and indications exist for HBOT. HBOT has been successfully used as adjunctive therapy for wound healing. Non-healing wounds such as diabetic and vascular insufficiency ulcers have been one major area of study for hyperbaric physicians where use of HBOT as an adjunct has been approved for use by way of various studies and trials. HBOT is also indicated for infected wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
89
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 9 publications
(23 reference statements)
0
89
0
5
Order By: Relevance
“…No protocol is available in veterinary medicine to standardize the number of treatments per day or total number of treatments for wound healing, although up to 3 hyperbaric oxygen sessions per day have been used in man. 35,36 The pressure, time of treatment, and frequency per day used in this study may have been insufficient to detect an observable effect on uncomplicated open and incisional wounds; however, the protocol used in this study was safe in this group of dogs, and an increase in pressure, treatment time, or frequency could increase the risk of adverse effects.…”
Section: Discussionmentioning
confidence: 89%
“…No protocol is available in veterinary medicine to standardize the number of treatments per day or total number of treatments for wound healing, although up to 3 hyperbaric oxygen sessions per day have been used in man. 35,36 The pressure, time of treatment, and frequency per day used in this study may have been insufficient to detect an observable effect on uncomplicated open and incisional wounds; however, the protocol used in this study was safe in this group of dogs, and an increase in pressure, treatment time, or frequency could increase the risk of adverse effects.…”
Section: Discussionmentioning
confidence: 89%
“…A series of small studies showed a more rapid healing and reduction of the amputations in patients treated with hyperbaric oxygen compared with control subjects. 16 The actual consensus recommendation is that hyperbaric oxygen therapy may be useful as adjuvant to standard presidium approach in the treatment of wounds in patients, but this field needs further investigation. Another treatment is the vacuum assisted closure (V.A.C.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular oxygen seems to play a central role in the wound healing process The hyperoxia caused by hyperbaric oxygenation (HBO) is responsible to increase tissue tolerance to ischemia, and improve biological defense mechanisms against free radicals, as well as the capacity of tissues to withstand ischemia 2 .…”
Section: Introductionmentioning
confidence: 99%